Efeito protetor da fucoidina, um inibidor de P e L-selectina, na resposta inflamatória sistêmica e distúrbios de motilidade gastrintestinal na pancreatite aguda experimental - Dias, Ana Carla da Silva Carvalho (2013)
Background & Aims: Neutrophils play a critical role in severe acute pancreatitis. Tissue infiltration of neutrophils in the pancreas is a multistep process, coordinated by specific adhesion molecules, such as P-selectin. Fucoidin is a sulphated fucosylated polysaccharide that binds to and blocks the function of L- and P-selectins, and the present study has evaluated whether fucoidin treatment could prevent neutrophil infiltration, and thereby reverse the systemic inflammation and gastrointestinal dysmotility associated with severe acute pancreatitis. Methods: Acute pancreatitis was induced in Swiss mice either by the retrograde infusion of taurolithocholic acid (3.0%) (TLC-S) into the pancreatic duct or by intraperitoneal injections of cerulein (50 µg/kg/h). The experimental groups received fucoidan (25 mg/kg, i.v.) before pancreatitis induction whist control groups received only saline. After 24 hours, pancreatic malondialdehyde (MDA), serum amylase, lipase, IL-1β, TNF- and nitrite were measured. In addition, myeloperoxidase (MPO) activity (lung, pancreas, stomach and jejunum) and histological assessment (pancreas) were determined. Gastric emptying and gastrointestinal transit (using the geometric center method) were also measured. Gastrointestinal contractility in vitro was recorded through force transducers coupled to a computerized data acquisition system, carbachol (0,01 µM – 30 µM), KCl 60mM and electrical field stimulation (0.5-8.0 Hz; 1ms; 40 V), was applied on gastric fundus and jejunum of mice 24 hours after TLC-S induced pancreatitis. Results: Pancreatic MDA, serum amylase, lipase, nitrite, TNF- and IL-1β, pancreatic and lung MPO, were increased in both TLCS- and cerulein acute pancreatitis compared with respective control groups. Fucoidan significantly decreased the augmented levels of amylase, lipase, pancreatic and lung MPO, MDA, TNF-, IL-1β and nitrite in both acute pancreatitis models. Pancreas histological changes observed in both models were significantly attenuated by fucoidan. The acute pancreatitis model induced by TLC-S caused delayed gastric emptying and gastrointestinal transit, incresead gastric and jejunum MPO, and jejunum hypercontractility in vitro. Fucoidan significantly reversed the gastrointestinal disorders in vivo and in vitro and augmented levels of gastric and jejunum MPO induced by TLC-S. Conclusion: Fucoidan reduced the severity of acute pancreatitis in mice by decreasing neutrophil infiltration, systemic inflammation and gastrointestinal dysmotility, suggesting that modulation of selectins may constitute a promising therapeutic approach for acute pancreatitis.